2022
DOI: 10.1017/wet.2022.56
|View full text |Cite
|
Sign up to set email alerts
|

The impact of electrocution treatments on weed control and weed seed viability in soybean

Abstract: Field experiments were conducted in 2020 and 2021 to determine the effectiveness of electrocution on several weeds commonly encountered in Missouri soybean production using an implement known as The Weed Zapper™. In the first study, the effectiveness of electrocution on waterhemp, cocklebur, giant and common ragweed, horseweed, giant and yellow foxtail, and barnyardgrass was determined. Electrocution was applied when plants reached average heights and/or growth stages of 30 cm, 60 cm, flowering, pollination, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
1
15
1
Order By: Relevance
“…Once the weeds became larger, the electrical applications were less effective because of the increased weed biomass that needed to be treated. This is contrary to previous research, which reported electrocution to be more effective at later plant growth stages (Schreier et al 2022).…”
Section: Palmer Amaranth Controlcontrasting
confidence: 99%
See 2 more Smart Citations
“…Once the weeds became larger, the electrical applications were less effective because of the increased weed biomass that needed to be treated. This is contrary to previous research, which reported electrocution to be more effective at later plant growth stages (Schreier et al 2022).…”
Section: Palmer Amaranth Controlcontrasting
confidence: 99%
“…Thus four weekly and two treatments, spaced 2 wk apart, were required for the 0.3- and 0.6-m application height, respectively, though only one treatment was required for the 0.9- and 1.2-m application heights. Schreier et al (2022) also observed increased weed control from multiple passes with the Weed Zapper. Hand weed removal consistently resulted in optimal weed control.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In Europe, the application of electric weed control with the Zasso ™ XPower with XPU applicator (continuous plant-electrode contact) at 3 km h −1 controlled 90% of A. artemisiifolia per year; the pollen from this plant is a common allergen in Europe, where an estimated 33 million people suffer from pollen allergies (Lake et al 2017;Trognitz et al 2020). In a separate study, Schreier et al (2022) found that electric weed control reduced weed seed viability by 54% to 80% in E. crus-galli, X. strumarium, A. artemisiifolia, S. faberi, A. trifida, S. pumila, and A. tuberculatus with the Weed Zapper ™ 6R30 (spark-discharge), as previously discussed. In this way, electric weed control can help reduce not only allergy symptoms but also agricultural weed seedbanks.…”
Section: Seed Effectssupporting
confidence: 66%
“…The booms also fold for transportation (Ruen 2018). The efficacy of the Weed Zapper ™ 6R30 unit was recently studied in a soybean crop by Schreier et al (2022), as previously discussed.…”
Section: The Weed Zapper ™mentioning
confidence: 98%